2019
DOI: 10.1097/j.pain.0000000000001525
|View full text |Cite
|
Sign up to set email alerts
|

Pain coping skills training for African Americans with osteoarthritis: results of a randomized controlled trial

Abstract: African Americans bear a disproportionate burden of osteoarthritis (OA), but they have been underrepresented in trials of behavioral interventions for pain. This trial examined a culturally tailored pain coping skills training (CST) program, compared to a wait list control group, among 248 African Americans with knee or hip OA. The pain CST program involved 11 telephone-based sessions over 3 months. Outcomes were assessed at baseline, 3 months (primary), and 9 months, and included the Western Ontario and McMas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(100 citation statements)
references
References 66 publications
(116 reference statements)
3
95
1
1
Order By: Relevance
“…Recent research on the effect of CBT on pain severity has shown mixed results and meta analyses show that the effect size on pain is small (Dixon et al 2007, Williams et al 2012. Some studies report substantial improvements in patients with knee osteoarthritis (Somers et al 2012, Cai et al 2018 while others report no effect on pain when comparing a CBT group with a usual care group (Helminen et al 2015, Broderick et al 2016, Allen et al 2019, Riddle et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on the effect of CBT on pain severity has shown mixed results and meta analyses show that the effect size on pain is small (Dixon et al 2007, Williams et al 2012. Some studies report substantial improvements in patients with knee osteoarthritis (Somers et al 2012, Cai et al 2018 while others report no effect on pain when comparing a CBT group with a usual care group (Helminen et al 2015, Broderick et al 2016, Allen et al 2019, Riddle et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Following this adaptation, a randomized controlled trial examined the effectiveness of the culturally-enhanced pain CST program, delivered via telephone over 3 months, among African Americans with OA. Participants who received the pain CST intervention had significant improvements in pain coping and arthritis self-efficacy, immediately following program completion, compared with a waitlist control group [14].…”
Section: Introductionmentioning
confidence: 94%
“…The STAART Study was a randomized controlled trial of 248 African Americans with symptomatic hip or knee OA [13,14]. Half of the participants were recruited from the University of North Carolina (UNC) Healthcare System and half were from the Durham Veteran Healthcare System (DVAHCS).…”
Section: Staart Study Overview and Participantsmentioning
confidence: 99%
See 2 more Smart Citations